1996
DOI: 10.1016/s1078-5884(96)80278-4
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen free radical and cytokine generation during endovascular and conventional aneurysm repair

Abstract: These results suggest that the ischaemia-reperfusion response associated with conventional aneurysm surgery may be largely negated by endovascular techniques. This may have significant consequences as the generation of oxygen free radicals and cytokines have been implicated in the development of systemic organ failure following aortic surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
61
0
5

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(69 citation statements)
references
References 36 publications
3
61
0
5
Order By: Relevance
“…Some workers have shown an increase in the inflammatory response following EVR, manifested as pyrexia, hypotension, and increased tumor necrosis factor alpha (TNF-␣) production, while others have found a reduction. [7][8][9][10] Although the ischemia-reperfusion injury sustained during EVR is less than that of OR, the endovascular technique causes significant leukocyte and platelet activation and may have an adverse effect on remote organ function. 7 Moreover, the radiological contrast medium used in EVR may have an effect on the host response, which is also not fully understood despite the well-documented nephrotoxicity of contrast agents.…”
mentioning
confidence: 99%
“…Some workers have shown an increase in the inflammatory response following EVR, manifested as pyrexia, hypotension, and increased tumor necrosis factor alpha (TNF-␣) production, while others have found a reduction. [7][8][9][10] Although the ischemia-reperfusion injury sustained during EVR is less than that of OR, the endovascular technique causes significant leukocyte and platelet activation and may have an adverse effect on remote organ function. 7 Moreover, the radiological contrast medium used in EVR may have an effect on the host response, which is also not fully understood despite the well-documented nephrotoxicity of contrast agents.…”
mentioning
confidence: 99%
“…The results of the present study indicate that sTM, similarly like VCAM-1 described above, may be a useful marker in monitoring endothelial injury occurring in the early postoperative period after OR. Some investigators have found that EVAR is associated with a lower induction of proinflammatory cytokines and oxidative stress rather than the conventional technique [38, 44, 45]. This fact may explain no difference between baseline and postoperative value of sTM after EVAR observed in present study, which result from its less damaging impact towards endothelial layer.…”
Section: Discussionmentioning
confidence: 40%
“…Biological markers of inflammatory pathways and stress responses such as proinflammatory cytokines, adrenaline, cortisol, and complement activity are reduced. [36][37][38] There is convincing evidence that EVAR is associated with reduced cardiac, respiratory, and renal complications, reduced need for blood transfusion and analgesia, shorter duration of surgery and postoperative hospital stay, lower need for intensive care, a faster return to normal function, and lower infection rates. 16 32 39-43 Until earlier this year, in the absence of evidence from large national randomised controlled trials, information on the efficacy of EVAR relied upon observational case series and data from large voluntary registries, such as the UK Registry for Endovascular Treatment of Aneurysms (RETA), and in particular, the European Collaborators on Stent Graft Techniques for Abdominal Aortic Aneurysm Repair (EUROSTAR) Registry.…”
Section: Existing Research and Continuing Trials In Evarmentioning
confidence: 99%